Editors’ Foreword (Vol. 50, Supplement) - Bretzke, Knut; Crassard, Rémy; Hilbert, Yamandú H. (Proceedings of the Seminar for Arabian Studies, 2020)
During the Seminar for Arabian Studies in July 2019 in Leiden, a special one-day session on the Stone Tools of Prehistoric Arabia was held. It gathered sixteen participants who delivered twenty-minute papers, with a broader attendance by the other participants of the Seminar. The present Supplement to Volume 50 of the Proceedings of the Seminar for Arabian Studies is the result of this Leiden session, presenting twelve articles on the lithic materials recently found in Arabia, all having been peer-reviewed and edited by the co-organizers and external reviewers.